(untitled) (Innovaciones Educativas, 2021)
In theory, educational systems have as their objective the formation of a citizenship that integrates actions and social commitments with the development of their personal well-being. However, in practice, we are witnessing educational situations contrary to this objective that provoke, in the best of scenarios, a formative weakness and, in the worst of cases, the constitution of a slave in modern times who abdicates the need of physical chains to submit to intellectual, cultural, social and economic chains. For this reason, and as a critical proposal that aims to warn of the complicity in this scenario on the part of the curricular designs, this essay carries out a conceptual discussion on the curriculum, critical pedagogy and the context of the curricular design. Later, it proposes some curricular principles for the implementation and consolidation of an oppressive educational system as a way to analyze and question the practice of curricular design. The development of the principles of curricular design allows the analysis, from a critical pedagogy and the rupture of the dominant technical discourse in this area, of the existence of manifest practices in the curricular structure that need to be questioned and transformed within the framework of the goal of developing democratic educational systems.